Model interpretation of the ionospheric F-region electron density structures observed by ground-based satellite tomography at sub-auroral and auroral latitudes in Russia in January–May 1999 - A. N. Namgaladze; O. V. Evstafiev; B. Z. Khudukon; A. A. Namgaladze; A. A. Namgaladze (Annales Geophysicae, 2003)
A satellite tomographic campaign was carried out in Russia during January–May 1999. The receiver chain consisted of four sites extending from the north of Karelia to the north of the Kola Peninsula. The F-region electron density measurements were performed during the main seasons (the winter, equinox and summer), and the data contained typical levels of solar activity (F10.7 varied from 100 to 200). The magnetic activity was quite low (Kp = 2 - 3). The Upper Atmosphere Model (UAM), the theoretical model of the Earth’s atmosphere, as well as two known empirical ionospheric models, IRI-95 and RIM-88, have been applied to compare with experimental data. The tomographic images were interpreted by using simulation results obtained by the models which were also compared to one another. The analysis shows the following: (a) all three models show the best agreement with the tomography data at the height 300 km (near hmF2) in comparison with the heights below and above hmF2 (200 and 400 km); (b) all three models systematically underestimate the electron density values in comparison with the tomography data at the height 200 km and overestimate them at the height 400 km; (c) for all investigated events the Ne (UAM) values are closest to Ne (tomo) in 399 of 1125 examined data points (36%), Ne(RIM-88) values are closest to Ne(tomo) in 510 cases (45%) and Ne (IRI-95) values are closest to Ne (tomo) in 216 cases (19%). For the only day-time events, the Ne (UAM) values are closest to Ne (tomo) in 274 of 624 data points (44%), whereas Ne (RIM-88) day-time values are closest to Ne (tomo) in 221 cases (36%) and closest to Ne (IRI-95) values in 129 cases (20%). It means that for all events RIM-88 has the best agreement with the tomography measured electron densities, whereas UAM has the best agreement with the daytime tomography measured electron densities, and IRI-95 has the worst agreement for both daytime and all events; (d) simulated UAM daytime values of electron density near the F2-layer maximum agree with corresponding tomography images for all seasons for the first half of 1999, covering almost the total range of the solar activity, so that no correction of the solar EUV flux (used as an input parameter in the UAM) is required; (e) a necessary correction of simulated precipitating soft electron flux intensities has to be made, in order to improve the consistency between measured night-time values of the electron density and those estimated by the theoretical model; (f) the simulated electron density behaviour caused by spatial, diurnal, seasonal variations, as well as due to a solar activity is consistent with the experimental tomographic images. This indicates a good reliability of both experimental and simulated data (at least in the central part of the examined latitudinal interval). Key words. Ionosphere (auroral ionosphere; modeling and forecasting)